A Novel LED Light Radiation Approach Enhances Growth in Green and Albino Tea Varieties - Zhang, Xianchen; Chen, Keyang; Zhao, Ziyi; Li, Siya; Li, Yeyun (Plants (Basel), 2023)
Light, as an energy source, has been proven to strongly affect photosynthesis and, thus, can regulate the yield and quality of tea leaves (Camellia sinensis L.). However, few comprehensive studies have investigated the synergistic effects of light wavelengths on tea growth and development in green and albino varieties. Thus, the objective of this study was to investigate different ratios of red, blue and yellow light and their effects on tea plants’ growth and quality. In this study, Zhongcha108 (green variety) and Zhongbai4 (albino variety) were exposed to lights of different wavelengths for a photoperiod of 5 months under the following seven treatments: white light simulated from the solar spectrum, which served as the control, and L1 (red 75%, blue 15% and yellow 10%), L2 (red 60%, blue 30% and yellow 10%), L3 (red 45%, far-red light 15%, blue 30% and yellow 10%), L4 (red 55%, blue 25% and yellow 20%), L5 (red 45%, blue 45% and yellow 10%) and L6 (red 30%, blue 60% and yellow 10%), respectively. We examined how different ratios of red light, blue light and yellow light affected tea growth by investigating the photosynthesis response curve, chlorophyll content, leaf structure, growth parameters and quality. Our results showed that far-red light interacted with red, blue and yellow light (L3 treatments) and significantly promoted leaf photosynthesis by 48.51% in the green variety, Zhongcha108, compared with the control treatments, and the length of the new shoots, number of new leaves, internode length, new leaf area, new shoots biomass and leaf thickness increased by 70.43%, 32.64%, 25.97%, 15.61%, 76.39% and 13.30%, respectively. Additionally, the polyphenol in the green variety, Zhongcha108, was significantly increased by 15.6% compared to that of the plants subjected to the control treatment. In addition, for the albino variety Zhongbai4, the highest ratio of red light (L1 treatment) remarkably enhanced leaf photosynthesis by 50.48% compared with the plants under the control treatment, resulting in the greatest new shoot length, number of new leaves, internode length, new leaf area, new shoot biomass, leaf thickness and polyphenol in the albino variety, Zhongbai4, compared to those of the control treatments, which increased by 50.48%, 26.11%, 69.29%, 31.61%, 42.86% and 10.09%, respectively. Our study provided these new light modes to serve as a new agricultural method for the production of green and albino varieties.